Analisis Pengaruh Leadership Styles, Work Environment, Dan Organizational Culture Terhadap Komitmen Organisasi Melalui Motivasi Kerja Sebagai Variabel Mediasi - Pratama, Diyan Adi; Suciningtyas, Santi; Ningsih, Diah Wuriah (Magister Manajemen STIE Bank BPD Jateng, 2025)
This study aims to analyze the influence of Work Leadership, Work Environment, and Organizational Culture on Organizational Commitment with Work Motivation as a Mediating Variable on Teachers at SMK Texmaco Pemalang. Sampling was done by purposive sampling so that 57 teachers were obtained as respondents. The study was conducted using quantitative descriptive research methods and SPSS V.25.0 analysis methods. Path analysis was used to analyze the data and the Sobel test to test mediation. The results of the path analysis showed that Work Leadership, Work Environment, and Organizational Culture had a direct, positive and significant effect on Organizational Commitment. Work Environment is the factor that contributes the most to Organizational Commitment. The results of the Sobel test showed that Work Motivation was able to mediate the relationship between Work Leadership, Work Environment, and Organizational Culture with Organizational Commitment. The implementation of appropriate Work Leadership, knowledge and experience, and a teacher's self in education have an impact on the effectiveness of teaching and learning. A good Work Environment and Organizational Culture with teachers' confidence in their abilities will contribute to the Organizational Commitment of teachers at SMK Texmaco Pemalang